Securing Space for Hospitality in a Settler-colonial City - Creagh, Robyn; Kerr, Thor; Cox, Shaphan; Ryder, P. (2016)
Rapid change in trade, demographics, culture and environment around the Indian Ocean demands a revaluation of how communities, sustainability and security are constituted in this globally strategically important region. Indian Ocean Futures: Communities, Sustainability and Security raises awareness of threats and opportunities beyond popular notions of communities through an examination of issues of concern to local, national, regional and transnational communities around the Indian Ocean Rim.